Evaluating the efficacy of serological testing of clinical specimens collected from patients with suspected brucellosis - Xu, Nannan; Qu, Chunmei; Sai, Lintao; Wen, Sai; Yang, Lulu; Wang, Shanshan; Yang, Hui; Liu, Hui; Wang, Gang (PLOS Neglected Tropical Diseases, 2023)
Author summary Brucellosis is an endemic zoonotic disease with significant impacts on public health worldwide. Early identification is crucial to reduce the rates of disability and mortality due to brucellosis. Human brucellosis is associated with a wide variety of clinical manifestations, making it difficult to diagnose clinically. Serological tests, which lack specificity and produce results that may be difficult to interpret, play a fundamental role in the diagnosis of this disease. Therefore, the combination of various serological tests may be helpful in ensuring the accuracy of diagnosis. Here, we aimed to explore the best combination among the SAT, ELISA and the Brucellacapt test to improve the efficiency of the diagnosis of human brucellosis.